Stable Methane Isotopologues From Northern Lakes Suggest That Ebullition Is Dominated by Sub‐Lake Scale Processes. Issue 10 (8th October 2020) - Wik, Martin; Thornton, Brett F.; Varner, Ruth K.; McCalley, Carmody; Crill, Patrick M.
Abstract: Stable isotopes have emerged as popular study targets when investigating emission of methane (CH4 ) from lakes. Yet little is known on how isotopic patterns conform to variations in emission magnitudes—a highly relevant question. Here, we present a large multiyear data set on stable isotopes of CH4 ebullition (bubbling) from three small adjacent subarctic lakes. The δ 13 C‐CH4 and δD‐CH4 range from −78.4‰ to −53.1‰ and from −369.8‰ to −218.8‰, respectively, and vary greatly among the lakes. The signatures suggest dominant hydrogenotrophic methanogenesis, particularly in the deep zones, but there are also signals of seemingly acetoclastic production in some high fluxing shallow areas, possibly fueled by in situ vegetation, but in‐sediment anaerobic CH4 oxidation cannot be ruled out as an alternative cause. The observed patterns, however, are not consistent across the lakes. Neither do they correspond to the spatiotemporal variations in the measured bubble CH4 fluxes. Patterns of acetoclastic and hydrogenotrophic production plus oxidation demonstrate that gains and losses of sediment CH4 are dominated by sub‐lake scale processes. The δD‐CH4 in the bubbles was significantly different depending on measurement month, likely due to evaporation effects. On a larger scale, our isotopic data, combined with those from other lakes, show a significant difference in bubble δD‐CH4 between postglacial and thermokarst lakes, an important result for emission inventories. Although this characteristic theoretically assists in source partitioning studies, most hypothetical future shifts in δD‐CH4 due to high‐latitude lake area or production pathway are too small to lead to atmospheric changes detectable with current technology. Plain Language Summary: Lakes are common in Arctic landscapes, and they are important sources of methane, a powerful greenhouse gas. Most of the lake methane that reaches the atmosphere is released by bubbling, a very erratic process in space and time. All methane is not the same, and the relative amounts of different types ("isotopologues") can show how and from what source a particular sample of methane was formed. In this study, which focuses on three lakes in northern Sweden, we analyze these different types of methane to determine if various methane‐creation and destruction processes can lead to different bubbling rates. We also considered how these processes differed spatially. We found that isotopologues alone do not explain why some parts of lakes bubble more than others. The measurements, however, do suggest that the shallow areas generally produce methane through processes that require more fresh organic material compared to the deeper zones where the sediments are more decomposed. This raises further questions whether certain species of aquatic plants contribute to the methane bubbling we observe and whether loss of methane in the sediments by oxidation is an important process in our lakes. Finally, we compare our results with studies of other types of northern lakes. Key Points: Stable isotopic signatures of CH4 bubbles vary greatly among and within three interconnected lakes Variability may be due to shifting isotopic signatures of source C and H plus methanogenic pathways overlaid with oxidation effects Stable isotopes provide little information on the spatial variation in CH4 ebullition rates